A Conceptual Model of the Influence of Luxury Values Perception in China - Sivapathy, Arunnaa (International Journal of Psychosocial Rehabilitation, 2019)
This research aims in order to investigate Chinese consumers’ intention behaviour by the TPB variables, which are attitudes, subjective norms, and perceived behavioural control. The model will be moderated by consumer knowledge and investigate the influence of luxury values on the purchase intention of Chinese consumers’. This study reviews the luxury value perception research that has been conducted in recent decades. This conceptual model is drawn using the conceptualization from Wiedmann (2007). This research needed a more comprehensive investigation in more developed countries or developing countries to develop a more complete picture. The results will help the marketers in planning, improving, and executing their marketing and communication strategies, and enlightening consumer behaviour in China. The research offered a wide range in understanding the Chinese luxury consumers’ reflections towards their luxury purchase intention. This provided a new theoretical perception towards the luxury values and contributed to the limited literature on the Chinese market concept.